Implementation of green new product development among SMEs: barriers and critical success factors - Abu, Noor Hidayah; Khoo, Kean Huat; Mansor, Mohd Fitri (EDP Sciences, 2018)
The phenomenon of outsourcing has spawned a rich body scholarly reseach in sveral decades. However, the answer to one of the pertinent question has remained elusive: Does cost reduction and business strategy really matters to the human resource outsourcing impacts. Looking at this question it is important for the organization to embark on the practice of human resource outsourcing to save operating cost and remain competitive. Therefore, the objective of this study is to investigate the effects of cost reduction and business starategy towards human resource outsourcing impacts. Both quantitative and qualitative methods were employed and the top management in Malaysian Government Link Companies (GLC’) is the unit of analysis. The findings revelaved that, both variables are significant statistically and non statically i.e from the experts opinion. Finally, the study also provides useful directions for future research, HR Practitioners and policy maker particularly in managing and organizing human reseouce matters.